P‐1.15: A new optical compensation scheme for AMOLED displays with a‐IGZO TFT and a‐Si:H PIN diode. (4th October 2019) - Wang, Ling; Lin, Yicheng; Zhu, Mingyi; Xu, Pan; Li, Zhengliang; Wu, Zhongyuan; Dong, Xue
Abstract : This paper proposed a new optical compensation scheme for AMOLED display based on a sensor unit in pixel. The sensor unit includes an a‐IGZO TFT, which is adopted as a switch due to its low off current, a‐Si:H PIN diode as optical sensor due to its high photoconductive gain, and a capacitor to store charges. Owing to the large off current difference under different brightness, the luminance of every pixel can be acquired by PIN sensor, and then data voltage is adjusted accordingly. The scheme is adopted in a 5 inch AMOLED display, and the results show this method can capture the pixel brightness accurately, and effectively compensate low gray level light uniformity.